Modified T-plate internal fixation in the treatment of medial malleolus fractures of the distal tibia in the elderly - Wang, Xipeng; Nie, Kun; Liu, Jiangtao; Jiang, Cong (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to compare the clinical efficacy of modified T-plate internal fixation vs. conventional cannulated lag screws in treating medial malleolus fractures of the distal tibia in elderly patients, with a focus on surgical outcomes, functional recovery, and complication profiles.MethodsA prospective cohort analysis was conducted on a sample of 46 elderly patients (aged ≥ 60 years) with isolated medial malleolus fractures treated at a single orthopedic center between April 2020 and December 2022. Patients were allocated to either modified T-plate internal fixation (n = 23) or cannulated lag screw internal fixation (n = 23). The postoperative conditions, including operative time, blood loss, and complications, as well as the long-term rehabilitation outcomes, such as AOFAS ankle and hindfoot score at 3, 6, and 12 months, were systematically compared.ResultsThe modified T-plate group exhibited significantly superior early functional recovery, with higher AOFAS ankle and hindfoot score at 3 months (63.5 ± 8.0 vs. 55.3 ± 13.3, P = 0.015) and 6 months (74.6 ± 8.9 vs. 67.8 ± 12.5, P = 0.041), though operative time was longer (85.6 ± 12.3 vs. 72.4 ± 10.8 min, P < 0.001). No significant differences were observed in intraoperative blood loss (120.5 ± 25.6 vs. 115.8 ± 22.4 ml, P = 0.511), overall complication rates (8.7% vs. 17.4%, P = 0.381), or long-term outcomes of AOFAS ankle and hindfoot score at 12 month (89.0 ± 8.7 vs. 87.9 ± 7.6, P = 0.628). Both groups demonstrated comparable safety profiles, with no severe complications during a mean 14.4-month follow-up.ConclusionModified T-plate fixation has been shown to facilitate early functional rehabilitation in elderly patients with distal tibial medial malleolus fractures. Although this method requires marginally longer operative time, it offers equivalent long-term outcomes and safety to traditional lag screws internal fixation. Notably, it is particularly advantageous for osteoporotic patients, as it addresses the challenges posed by bone fragility and compromised healing capacity.